2021
DOI: 10.1016/j.vph.2021.106873
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles (EVs) in ischemic conditioning and angiogenesis: Focus on endothelial derived EVs

Abstract: During myocardial ischemia, timely reperfusion is critical to limit infarct area and the overall loss of cardiac contractile function. However, reperfusion further exacerbates the damage of the ischemic heart. This type of injury is known as ischemia-reperfusion injury (IRI). Ischemic conditioning is a procedure which consists of brief cycles of ischemia and reperfusion in order to protect the myocardium against IRI. Remote ischemic conditioning (RIC), namely transient brief episodes of ischemia at a remote si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 70 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…EVs are involved in the process of cardiovascular pathology, the communication between cardiomyocytes, fibroblasts, smooth muscle cells and endothelial cells, and the regulation of cardiac regeneration, ventricular remodeling and angiogenesis ( 22 24 ). Cardiomyocytes are the main cells of the heart and their EVs play different roles in myocardial repair ( 25 ).…”
Section: Mechanism Of Evs Repairing Damaged Myocardiummentioning
confidence: 99%
“…EVs are involved in the process of cardiovascular pathology, the communication between cardiomyocytes, fibroblasts, smooth muscle cells and endothelial cells, and the regulation of cardiac regeneration, ventricular remodeling and angiogenesis ( 22 24 ). Cardiomyocytes are the main cells of the heart and their EVs play different roles in myocardial repair ( 25 ).…”
Section: Mechanism Of Evs Repairing Damaged Myocardiummentioning
confidence: 99%
“…Beside cardioprotective miR-126 and miR-199a [ 61 ] and pro-proliferative miR-25, miR-186, and miR-221 [ 71 ], BEC-EVs transfer a plethora of further miRNAs, yRNA fragments [ 71 ], and lncRNAs [ 73 ]. Cardioprotective EV properties could be hampered by caveolin-1 exosomes from interleukin-3 (IL-3)-stimulated BECs [ 74 ]. In vitro, EC morphology also regulates inflammatory response, as EVs from elongated BECs carry markedly higher amounts of anti-inflammatory miR-10a [ 75 ].…”
Section: Molecular Signatures Of Endothelial Cells and Endo-evsmentioning
confidence: 99%
“…In addition, some studies have suggested that EEVs carry messages which may influence endothelial cells' reaction to atherogenic insults. Therefore, they could be considered a novel target for the modulation of CVD progression [ 44 , 45 ]. The paucity of studies and their heterogeneity do not allow to draw clear conclusions on this intriguing hypothesis.…”
Section: Biomarkers: From the Oldest To The Newestmentioning
confidence: 99%